Yan-Kit So: Classic Food of China - D., J.M. (Petits Propos Culinaires, 1992)
Yan-Kit So: Classic Food of China: Macmillan, London, 1992: 387 pp, colour photographs, black and white reproductions, index, bibliography, glossary, £25.00.